Rapid Accumulation of Total Lipid in Rhizoclonium africanum Kutzing as Biodiesel Feedstock under Nutrient Limitations and the Associated Changes at Cellular Level - Gour Gopal Satpati; Sanjit Kanjilal; Rachapudi Badari Narayana Prasad; Ruma Pal (International Journal of Microbiology)
Increase of total lipid and the proportion of the favorable fatty acids in marine green filamentous macroalga Rhizoclonium africanum (Chlorophyceae) was studied under nitrate and phosphate limitations. These stresses were given by both eliminating and doubling the required amounts of nitrate and phosphate salts in the growth media. A significant twofold increase in total lipid (193.03 mg/g) was achieved in cells in absence of nitrate in the culture medium, followed by phosphate limitation (142.65 mg/g). The intracellular accumulation of neutral lipids was observed by fluorescence microscopy. The scanning electron microscopic study showed the major structural changes under nutrient starvation. Fourier transform infrared spectroscopy (FTIR) revealed the presence of ester (C-O-C stretching), ketone (C-C stretching), carboxylic acid (O-H bending), phosphine (P-H stretching), aromatic (C-H stretching and bending), and alcohol (O-H stretching and bending) groups in the treated cells indicating the high accumulation of lipid hydrocarbons in the treated cells. Elevated levels of fatty acids favorable for biodiesel production, that is, C16:0, C16:1, C18:1, and C20:1, were identified under nitrate- and phosphate-deficient conditions. This study shows that the manipulation of cultural conditions could affect the biosynthetic pathways leading to increased lipid production while increasing the proportion of fatty acids suitable for biodiesel production.